O1-S05.05 Association between Trichomonas vaginalis and vaginal bacterial community composition among asymptomatic reproductive-age women in the USA. (10th July 2011) - Brotman, R; Jones, L L; Sakamoto, J; Gajer, P; Ault, K; Peralta, L; Forney, L; Abdo, Z; Ravel, J
Abstract : Background: Vaginal bacterial communities are thought to prevent infection by sexually transmitted organisms. Prior work demonstrated that the vaginal microbiota of reproductive-age women in the US cluster into five groups of bacterial communities; four dominated by Lactobacillus spp . ( L iners, L crispatus, L gasseri, L jensenii ), and one lacking significant numbers of lactobacilli and characterised by higher proportions of strictly anaerobic organisms (termed group IV). We sought to compare the vaginal microbiota of T vaginalis -positive and T vaginalis -negative women using cultivation-independent methods. To our knowledge, this is the first analysis of the relationship between T vaginalis and vaginal bacterial communities characterised by molecular methodologies. Methods: Self-collected vaginal swabs were obtained cross-sectionally from 396 asymptomatic US women equally representing four ethnic/racial groups. Screening for the presence of T vaginalis was performed using PCR targeting the 18S rRNA and ß-tubulin genes. Vaginal bacterial composition was characterised by pyrosequencing of barcoded 16S rRNA genes. The relationship between vaginal microbiota and T vaginalis was evaluated by Fisher's exact testing and logistic regression. Results: Of the 11 T vaginalis -positive cases, 8 (72%) were classified to the low-Lactobacillus group IV, 2 (18%) and 1 (9%) with communities dominated by L iners and L crispatus, respectively (p value: 0.056). Group IV was associated with an eightfold increased odds of detecting T vaginalis compared to women with communities dominated by L crispatus (OR: 8.26, 95% CI: 1.07% to 372.65%, p value: 0.04). Other than the major bacteria dominating each cluster, none of the other observed taxa showed significant association with T vaginalis -positivity although this may reflect few observed cases rather than lack of a true association. Ten (91%) of the T vaginalis cases self-reported Black ethnicity and 1 (9%) reported Asian, (p value: 0.00002). Conclusion: Molecular analyses revealed that vaginal microbiota with low proportions of lactobacilli were significantly associated with presence of T vaginalis . Longitudinal studies are needed to identify the causal nature of the relationship between vaginal bacterial communities and STI risk.